Inclusion as Ethics, Equity and/or Human Rights? Spotlighting School Mathematics Practices in Scotland and Globally - Swanson, Dalene M. (2017)
Mathematics education has been notoriously slow at interpreting inclusion in ways that are not divisive. Dominant views of educational inclusion in school mathematics classrooms have been shaped by social constructions of ability. These particularly indelible constructions derive from the perceived hierarchical nature of mathematics and the naturalised assumption that mathematisation is purely an intellectual exercise. Constructions of ability, therefore, emanate from the epistemic structures of mathematics education as predominantly practiced worldwide, and the prevalence of proceduralism and exclusion in those practices. Assumptions about ‘ability’ have become a truth to mathematical aptitude held by mathematics teachers in schools. This includes schools across Scotland. In Scotland, the government owes the ‘included pupil’ a legal obligation to provide additional support for learning under section 1(1) of the Education (Additional Support for Learning) (Scotland) Act 2004. However, classroom practices deployed around socially-constructed notions of ability have seen schools moving away from an emphasis on ‘additional’ to an expansive interpretation of ‘different from’ in the language of section 1(3)(a) of the Act 2004. This shift, therefore, reinstalls exclusionary effects to school mathematics practices by creating the conditions for some pupils, constructed in terms of disabilities or low ability, to be afforded a more inferior education than others. While philosophical conversations around whether these practices are ethical, egalitarian or democratic might ensue, there is also the human rights angle, which asks whether such practices are even lawful.